THE SOLUTION OF THE ALGORITHM FOR SOLVING THE DIMENSIONAL CHAINS DURING THE DESIGNING COURSE - Liviu Marius CÎRŢÎNĂ; Constanţa RĂDULESCU (Fiabilitate şi Durabilitate)
The methodology of solving the designing problems and calculus formulasdependent upon the way of showing the sourcing data and the required results of the calculus. Thegiven operative dimensional chain is made up of three primary constitutive elements, respectivelyof the closing element. When solving the designing problem the rated size of the determinativeelement shall be circled and checked up, without exceeding the limit values of the calculus of theclosing element, since they are its regulating values. As a result solving the size chain nthe ratedvalue of the constitutive element shall be found out. At such a rated value, the closing elementshall be made up within the regulating limits of the reserve on the lower, respectively upperlimits. If the reserve on the tolerance of the closing element ist else than zero, then the output ofthe actual values of the closing elements on the settled limits cannot be avoided. If the reserve onthe tolerance of the closing element ist equal withn zero, then the rounding off of the rateddetermined value of this chain could not be possible.